Efficient Resource Allocation Algorithm in Dependable Distributed Computing Systems Using A Colony Optimization - Yogi, Manas Kumar; Kumari, G; Yamuna, L (International Journal of Computer Sciences and Engineering, 2025)
In this paper we present efficient resource allocation algorithm which give rise to economic models for job scheduling in distributed computing environmental. Existing schemes which schedule jobs in such a environment have their routes in searching of time slots in resource occupancy schedules which consider only the time slot sets. Our algorithm proposes a hybrid time slot search algorithm and configures each job in an efficient schedule.